Direct Comparison of the Safety and Efficacy of Ferric Carboxymaltose versus Iron Dextran in Patients with Iron Deficiency Anemia. (29th August 2013) - Hussain, Iftikhar; Bhoyroo, Jessica; Butcher, Angelia; Koch, Todd A.; He, Andy; Bregman, David B.
Abstract : Several intravenous iron complexes are available for the treatment of iron deficiency anemia (IDA). Iron dextran (DEX) is associated with an elevated risk of potentially serious anaphylactic reactions, whereas others must be administered in several small infusions to avoid labile iron reactions. Ferric carboxymaltose (FCM) is a nondextran intravenous iron which can be administered in high single doses. A randomized, open label, and multicenter comparison of FCM to DEX in adults with IDA and baseline hemoglobin of ≤11.0 g/dL was conducted. A total of 160 patients were in the safety population (FCMn = 82 ; DEXn = 78 ). Adverse events, including immune system disorders (0% in FCM versus 10.3% in DEX, P = 0.003 ) and skin disorders (7.3% in FCM versus 24.4% in DEX, P = 0.004 ), were less frequently observed in the FCM group. A greater portion of patients in the FCM group experienced a transient, asymptomatic decrease in phosphate compared to patients in the DEX group (8.5% in FCM versus 0% in DEX, P = 0.014 ). In the FCM arm, the change in hemoglobin from baseline to the highest observed level was 2.8 g/dL, whereas the DEX arm displayed a change of 2.4 g/dL (P = 0.20 ). Treatment of IDA with FCM resulted in fewer hypersensitivity-related reactions than DEX.